Times Limited Accountable Anonymous Online Submission Control System from Single-Verifier k-times Group Signature - Zhao, X.; Zhang, F. (Informatica)
Times Limited Accountable Anonymous Online Submission Control System from Single-Verifier k-times Group Signature